Cultural learning in Finnish primary and secondary schools : examining Låna en Nordbo’s method - Petersen, Camilla (My University, 2019)
In this thesis the use case of the multicultural education programme, Låna en Nordbo, will be examined. The need for multicultural education is becoming in bigger demand in the continuous globalising world, as school classes become more diverse and the business world is expanding across borders. Therefore, intercultural skills and competencies are needed in the future. The question of the importance of multicultural education and intercultural communications is investigated, in order to discover if Låna en Nordbo has success in achieving its objectives in educating about other Nordic cultures to Finnish primary and secondary school students. The case of the Låna en Nordbo programme is interesting in the manner that it brings something new to the school curriculum in Finland. Schools who are visited do not have vast engagement with other Nordic countries, and in some cases the students have never visited the country in focus, nor met a person from that country. Where the programme is meeting obstacles in the instance of keeping the attention of the students throughout the presentations, as well as the language of delivery i.e. Swedish, as it is not the mother tongue of a majority of the teachers of the programme, nor the students. The lack of understanding is one of the factors preventing the programme in succeeding. Another factor is the delivery of the content as not all teachers have been presenting to or teaching students in the age groups they were faced with before. This poses a challenge to keep the students interested throughout the entire presentation, and to make the country presented relevant to them. The suggestion to combat this is that the Nordic Culture Point would provide the teachers with a seminar on teaching the students that they will visit, as well as making the presentation more interactive by engaging the students’ electronic devices that they use on a daily basis. The latter suggestion is based on the observation that the students tended to use their electronic devices during the presentation.
Keywords: multicultural education, intercultural communications, communications, culture, Finnish education, Nordic Culture Point, Låna en Nordbo, globalisation, intercultural skills, intercultural competencies, Finnish primary education, Finnish secondary education, electronic devices in teaching, cultural learning.